Correlation of Butterfly (Lepidoptera: Papillionoidea) With Flowering Plant In The Bodogol Nature Conservation Education Center, Mount Gede Pangrango - Hasni Ruslan; Yenisbar Yenisbar; Abda’u Satiyo (Journal of Tropical Biodiversity, 2023)
Butterflies are one type of insect that functions as a pollinator. Research on butterflies in the Bodogol Nature Conservation Education Area (PPKAB), has already been published, but research on the correlation of butterflies with flowering plants has not yet been published. The purpose of this study was to determine the correlation between butterflies and flowering plants in the PPKB area. The research was conducted in February-June 2022 in heterogeneous and homogeneous forests. The research was conducted using purposive sampling method. In each observation, 10 plots were observed in heterogeneous on 3 lanes (Rasamala, Canopi, and Aprika), and in homogeneous forest on 3 lanes (Cikaweini-Cipadaranten, and Gembong koneng). Research using cameras and insect nets. In this study, 78 species, 4 families with 261 individuals were found in heterogeneous forests, and 39 species, 5 families with 158 individuals in homogeneous forests. Butterfly families: Papilionidae, Pieridae, Nymphalidae, Lycenidae, and Rionidae. The Nymphalidae family is one of the families with the highest number of species and individuals compared to other families. Based on the index value of butterfly diversity, it is classified as high (heterogeneous) and medium (homogeneous). High evenness index in both habitats. Jamides celeno is one of the dominant species in both habitats. Correlation analysis showed that there was a strong relationship between flowering plants and the number of individual butterflies in both habitats (heterogeneous and homogeneous).